(untitled) (REVISTA NODO, 2026)
Sculptor Maribel Portela (Mexico City, 1960) presented Arboleda sonora at the Museum of Modern Art in Mexico City from March to June 2024. Art critic Irving Domínguez analyzes the forty-five pieces that were part of this exhibition.